Management of colorectal laterally spreading tumors: a systematic review and meta-analysis - Russo, Pedro; Barbeiro, Sandra; Awadie, Halim; Libânio, Diogo; Dinis-Ribeiro, Mario; Bourke, Michael (Endoscopy International Open, 2019)
Abstract Objective and study aims To evaluate the efficacy and safety of different endoscopic resection techniques for laterally spreading colorectal tumors (LST). Methods Relevant studies were identified in three electronic databases (PubMed, ISI and Cochrane Central Register). We considered all clinical studies in which colorectal LST were treated with endoscopic resection (endoscopic mucosal resection [EMR] and/or endoscopic submucosal dissection [ESD]) and/or transanal minimally invasive surgery (TEMS). Rates of en-bloc/piecemeal resection, complete endoscopic resection, R0 resection, curative resection, adverse events (AEs) or recurrence, were extracted. Study quality was assessed with the Newcastle-Ottawa Scale and a meta-analysis was performed using a random-effects model. Results Forty-nine studies were included. Complete resection was similar between techniques (EMR 99.5 % [95 % CI 98.6 %-100 %] vs. ESD 97.9 % [95 % CI 96.1 – 99.2 %]), being curative in 1685/1895 (13 studies, pooled curative resection 90 %, 95 % CI 86.6 – 92.9 %, I 2 = 79 %) with non-significantly higher curative resection rates with ESD (93.6 %, 95 % CI 91.3 – 95.5 %, vs. 84 % 95 % CI 78.1 – 89.3 % with EMR). ESD was also associated with a significantly higher perforation risk (pooled incidence 5.9 %, 95 % CI 4.3 – 7.9 %, vs. EMR 1.2 %, 95 % CI 0.5 – 2.3 %) while bleeding was significantly more frequent with EMR (9.6 %, 95 % CI 6.5 – 13.2 %; vs. ESD 2.8 %, 95 % CI 1.9 – 4.0 %). Procedure-related mortality was 0.1 %. Recurrence occurred in 5.5 %, more often with EMR (12.6 %, 95 % CI 9.1 – 16.6 % vs. ESD 1.1 %, 95 % CI 0.3 – 2.5 %), with most amenable to successful endoscopic treatment (87.7 %, 95 % CI 81.1 – 93.1 %). Surgery was limited to 2.7 % of the lesions, 0.5 % due to AEs. No data of TEMS were available for LST. Conclusions EMR and ESD are both effective and safe and are associated with a very low risk of procedure related mortality.